Reversibility of Antipsychotic-Induced Weight Gain: A Systematic Review and Meta-Analysis - Speyer, Helene; Westergaard, Casper; Albert, Nikolai; Karlsen, Mette; Stürup, Anne Emilie; Nordentoft, Merete; Krogh, Jesper (Frontiers in Endocrinology, 2021)
Abstract Background and aims: Weight gain is a major adverse effect of antipsychotic medication, affecting physical and mental wellbeing negatively. The objective was to explores if deprescribing antipsychotic medication could reverse the weight gain. Methods: Controlled and uncontrolled studies reporting the effect deprescribing (in this study defined as discontinuation, dose reduction, switch to a partial agonist (aripiprazole) or switch from polypharmacy to monotherapy) on weight was included. Primary outcome was difference in weight between deprescribed and maintenance groups based on controlled studies. Secondary outcomes were change in weight from pre-deprescribing to end of follow-up based on uncontrolled studies and interventional groups. Results: We identified 51 studies, 40 were randomized controlled trials. We found that weight in deprescription groups were 1.55 kg (95% CI -2.08 to -1.02; <0.001) lower than in maintenance groups based on 40 controlled trials. The weight change from pre to post was a reduction of 1.23 kg (95% CI -1.55 to -0.90; p<0.001) based on 51 studies. Conclusion: We found a statistically, but not clinically, significant effect of deprescription. There were substantial limitations in the generalizability and further research is needed to address this important issue properly.